RAPAKIVI GRANITE-ANORTHOSITE ASSOCIATION OF THE EASTERN EUROPEAN CRATON - MYTROKHYN, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2024)
The systematic description of the most typical rapakivi granite-anorthosite complexes of the East Europe craton is resulted in the article. The aria distribution, mode of occurrence, geology and composition are analysed. Abjection of two regional rapakivi granite-anorthosite provinces is proved. The volume and petrographic composition of the association is determined at a modem level.